Changes in The Values Of Local Fishing Wisdom Among The Community Of Harapan Island Village - Siti Kotijah; Febri Noor Hediati; Ine Ventyrina; Agustinawati; Nor Aprilia; Hairan; Poppilea Erwinta (Universitas Islam Lamongan, 2026)
This study examines fishing practices in Pulau Harapan Village, Muara Muntai District, focusing on the application of local wisdom and its relationship to fisheries law. This village relies largely on river fisheries for its livelihood, utilizing traditional fishing gear such as nets, seines, traps, and longlines, which are selective and environmentally friendly. However, over time, there has been a shift in values ​​in fishing practices, marked by the emergence of destructive fishing gear such as electric shocks. This study uses the Socio-Legal Research (SLR) method, combining normative studies and empirical data through observations and interviews with the fishing community. The results show that local wisdom still plays a role in maintaining the sustainability of fisheries resources, but economic factors, limited education, and weakened social control encourage some fishermen to switch to environmentally unfriendly methods. Violations are generally resolved through a restorative justice approach due to the absence of formal customary institutions regulating fisheries management in the village. Therefore, strengthening local wisdom values, increasing supervision, and implementing more effective laws are needed to maintain the sustainability of the Mahakam River ecosystem.